Proceedings of the Proceedings of the 7th Mathematics, Science, and Computer Science Education International Seminar, MSCEIS 20 2020
DOI: 10.4108/eai.12-10-2019.2296314
|View full text |Cite
|
Sign up to set email alerts
|

The Course of Biology Learning Methodology: Are Concept-Based Learning and Drill Method Effective in Enhancing Higher-Order Thinking Skills of Students?

Abstract: This research aimed to enhance the students' higher-order thinking skills through the Concept-Based Learning and Drill Method in The Course of Biology Learning. The concept-based learning leads students to know the basic concept and avoiding misconceptions, while the drill method is unique due to its characteristics, which make students think higher than before. Therefore, the combination of concept-based learning and drill method was applied in the course of Biology Learning Methodology as an attempt to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In learning, teachers as the spearhead in the world of education were required to create an effective and communicative learning environment by paying attention to learning components, one of which was learning methods and learning media. Learning methods were techniques used by teachers to achieve learning objectives when delivering learning subject (Darmadi in Lufri et al, 2020). The methods used in implementing extracurricular journalism were Project Learning and Problem-Based Learning which consists of discussions, introduction to 5W + 1 H, writing practice, interview practice, news reporting practice, and live practice.…”
Section: Implementation Of the Journalism Extracurricular Programmentioning
confidence: 99%
“…In learning, teachers as the spearhead in the world of education were required to create an effective and communicative learning environment by paying attention to learning components, one of which was learning methods and learning media. Learning methods were techniques used by teachers to achieve learning objectives when delivering learning subject (Darmadi in Lufri et al, 2020). The methods used in implementing extracurricular journalism were Project Learning and Problem-Based Learning which consists of discussions, introduction to 5W + 1 H, writing practice, interview practice, news reporting practice, and live practice.…”
Section: Implementation Of the Journalism Extracurricular Programmentioning
confidence: 99%
“…Prior research has indicated the importance of active and interactive learning strategies in addressing difficulties related to recalling scientific terms and comprehending concepts (Apodaca et al, 2019;Lufri et al, 2020;Mazowiecki-Kocyk, 2021).…”
Section: Challenges Faced By Students In Biology Learningmentioning
confidence: 99%